Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Keputusan Pembelian: (Survei Pada Konsumen Sepatu Merek Adidas Di Toko Kaki Gaya Kota Tasikmalaya) - Tika Yupitasari (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine the simultaneous and partial effect of product quality and service quality on purchasing decisions for Adidas brand shoes at the Gaya Foot Shop, Tasikmalaya City. The method used in this research is a survey method with a quantitative approach. The population studied were 100 respondents. The data collected in the form of primary data and secondary data. Data analysis in this study used multiple linear regression analysis using SPSS veris 24 software. The results showed that product quality and service quality simultaneously had a significant effect on purchasing decisions for Adidas brand shoes at the Gaya Foot Shop, Tasikmalaya City. Product quality, partially does not have a significant effect on purchasing decisions for Adidas brand shoes at the Gaya Foot Shop, Tasikmalaya City. Service quality, partially has a significant effect on purchasing decisions for Adidas brand shoes at the Gaya Foot Shop, Tasikmalaya City